A DEVELOPMENTAL PERSPECTIVE ON CYBERBULLYING: RISK FACTORS, SOCIAL-COGNITIVE DEFICITS, AND INTERVENTION STRATEGIES - John Ratu; Anjali Singh; Laisa Tawake (International Journal of Educatio Elementaria and Psychologia, 2026)
Cyberbullying has emerged as a significant issue affecting children and adolescents, with potentially severe emotional, social, and psychological consequences. Understanding the developmental factors that contribute to cyberbullying is essential for creating effective prevention and intervention strategies. This study explores the risk factors, social-cognitive deficits, and intervention strategies associated with cyberbullying from a developmental perspective. The research aims to identify key risk factors contributing to cyberbullying behaviors, explore how social-cognitive deficits influence both perpetrators and victims, and evaluate the effectiveness of various intervention strategies. A mixed-methods approach was employed, including surveys, interviews, and psychological assessments, to gather data from 300 adolescents (ages 12-18) across diverse socioeconomic backgrounds. The results revealed that lower levels of emotional regulation, impaired empathy, and poor problem-solving skills were significant predictors of both perpetration and victimization in cyberbullying. Furthermore, interventions focusing on emotional intelligence, empathy training, and peer support were found to be effective in reducing cyberbullying behaviors. The study concludes that a comprehensive, developmental approach addressing social-cognitive skills is essential for preventing and mitigating the impacts of cyberbullying, emphasizing the importance of early intervention and continuous support in school environments.